Smart Rack Inventory Berbasis RFID Untuk Manajerial Gudang - Muharramsyah, Iqbal Fadjar; Mu'Arif, Samsul; Dwijotomo, Abdurahman; Kamarudin, Kamarudin; Ridwan, Ridwan (Journal of Applied Electrical Engineering, 2024)
In warehouse management within the industry, there are often condition named stock-opname where physical stock and recorded stock do not match. This discrepancy can be caused by human error, as most of the input process work is still performed manually. To address this issue, this research developed Smart Rack Inventory capable of detecting items stored on the rack based on the RFID codes attached to the stored items. Additionally, an interactive web interface is utilized for managing storage and retrieving information about stored items. From the test results, the tool can easily record and display stored items with RFID tags when the orientation of the RFID sticker on the items aligns with the RFID sensor in the designed rack system. The success rate reached 100% at a distance of 60 cm. However, when the sticker's position is not aligned with the RFID sensor, where the RFID tag faces a direction opposite to the sensor, the smart rack system encounters difficulties in detecting and recording the item.